The Needs of English for Islamic Studies (EIS) in Traditional and Modern Pesantren - Alfinda, Rio; Humaira, Radhia (UIII Press, 2023)
This research aims to analyze the needs, English skill levels, and necessities of students in English language learning when undertaking Islamic studies. Designed as quantitative-descriptive, the researchers use survey methodology by distributing questionnaires to students. The results regarding English fluency show that their English competence needs improvement. Their ability needs to be improved in four skills (speaking, listening, reading and writing). In the context of items necessary for English for Islamic Studies (EIS) courses, the results indicate that the students highlight two skills that they see as needed in EIS: speaking and reading.